Distributed renewable energy management: A gap analysis and proposed blockchain-based architecture - Annegret Henninger; Atefeh Mashatan (Journal of Risk and Financial Management, 2022)
The heterogeneous and decentralized nature of renewable energy sources is too much to handle for traditional and centralized IT grid infrastructure. Blockchain technology can address many of the associated challenges. This paper provides an overview of the state-of-the-art technology layers of grid system infrastructure, a proposed future state using blockchain technology, and gap analysis. The paper also contributes a set of architectural requirements for a blockchain-enabled future state and a proposed hybrid architecture using blockchain technology, verifiable credentials, and smart contracts. This architecture can uniquely support the technology layers critical to renewable energies, including system architecture, registries, grid management, billing, privacy, and interoperability.
Keywords: 650; blockchain; decentralized IDs (DID); grid management; IT architecture; IT infrastructure; microgrid; P2P; renewable energy; smart grid; verifiable credentials (VC)